Paisaje urbano y espacio público como expresión de la vida cotidiana (2018)
Given that urban landscape is the expression of everything perceivable in a city’s public spaces, the analysis of urban attributes allows identifying patterns, sequences, and units in the urban landscape that lead to establishing design criteria in terms of visual quality. The paper proposes to study the attributes of the visual and functional quality of urban landscapes, including physical attributes: physical-spatial configuration, activities, biodiversity and diversity; as well as psychological attributes: physical integrity and aesthetic expression, which are applied to the assessment and design of public spaces in a sector of the historic center of the city of Mérida (Venezuela). The methodological approach of the multidimensional construction of urban landscapes is used to explain conceptual aspects that affect the perception of public spaces, in relation to the attributes of urban space. This assumption suggests further aspects that demonstrate its usefulness for future research and design proposals on urban landscape